PHYSICOCHEMICAL AND SENSORY CHARACTERISTIC EVALUATION OF SAGO FLOUR COOKIES WITH STEVIA SUGAR (Stevia Rebaudiana) ADDITION - Anita, Elva; Safrida, Safrida; Muchdatul Ayunda, Hanif; Alamsyah , Teuku (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
Cookies are a practical snack and are enjoyed by various age groups. Modifying sago flour cookies with stevia sugar not only has a crunchy texture and a preferred taste, but is also healthier. This study aims to determine the effect of various concentrations of sago flour with the addition of stevia sugar on cookies' physicochemical and sensory properties. This study used an experimental design with a quantitative approach and a Completely Randomized Design (CRD). The treatment consisted of four compositions: P1 (100% wheat flour: 0% sago flour) as a control, P2 (50% wheat flour: 50% sago flour), P3 (25% wheat flour: 75% sago flour), and P4 (0% wheat flour: 100% sago flour). Observations made were sensory tests, including: color, aroma, taste, texture, and crispness. Nutritional content tests included: water content, ash content, and fat content. Physical tests included: Hardness test. Respondents in the sensory test were 70 untrained panelists. Based on the research results, cookies substituted with 75% sago flour (P3) produced the highest acceptance of aroma, taste, texture, and crispness compared to other treatments, respectively, namely 3.86 (like), 3.66 (like), 3.87 (like), and 3.74 (like). The cookie hardness test found that the higher the proportion of sago flour, the more complex the cookies produced, namely P2 of 8.22 N/mm2, P3 of 8.4 N/mm2, and P4 of 11.5 N/mm2. Then, in the water content test, the more the proportion of sago flour, the more significant (P<0.05) the water content was, namely 4.42% (P2), 5.54% (P3), and 7.56% (P4). Meanwhile, the total ash and fat content decreased significantly (P<0.05), respectively, namely 0.88% (P2), 0.48% (P3), 0.30% (P4) ash content, and 29.09% (P2), 25.51% (P3), 21.04% (P4) fat content. The water, ash, and fat content in sago flour cookies meet the quality requirements of SNI 01-2973-2022 cookies except for the water content of the P4 treatment. Thus, the cookie formulation with 75% sago flour, 25% wheat flour, with the addition of stevia sugar (P3) produces the best product based on organoleptic acceptance and cookie quality requirements. However, it is necessary to identify the shelf life test of sago cookies to ensure the quality and safety of the product.